In situ strain tuning of the metal-insulator-transition of Ca2RuO4 in angle-resolved photoemission experiments - S. Riccò (Nature Portfolio, 2018)
The role of the lattice in the correlated metal-insulator transition of Ca2RuO4 has led to significant interest but experiments that are at the same time sensitive to crystal and electronic structure are difficult. Riccò et al. successfully combine ARPES measurements with in situ strain tuning across the Mott transition.